THE IMPORTANCE OF CYBERSECURITY AWARENESS FOR CHILDREN - Yuliana Yuliana (Lampung Journal of International Law, 2022)
During the COVID-19 pandemic, the shift to online schooling increased children's vulnerability to cyberattacks and malware. Consequently, cultivating cybersecurity awareness among children is essential. Moreover, engaging with online games and stories can lead children to neglect their studies, underscoring the need for balanced internet usage. This paper highlights the importance of cybersecurity awareness among children, employing a literature review methodology. The results indicate that cybersecurity awareness among children can be effectively enhanced through digital literacy training. Programs should educate children on how to avoid risky behaviors online, including interactions susceptible to phishing, exposure to inappropriate content such as pornography, cyberbullying, identity theft, and privacy breaches. Additionally, children must learn the importance of keeping their passwords secure and private and adopting a cautious approach while playing online games. In conclusion, digital literacy and cybersecurity programs are not only teachable to children but are also crucial for boosting their cybersecurity awareness.